Traditional Chinese medicine to improve immune imbalance of asthma: focus on the adjustment of gut microbiota - Lu, Ke; Li, Chen; Men, Jingwen; Xu, Bin; Chen, Yang; Yan, Peizheng; Gai, Zhibo; Zhang, Qingxiang; Zhang, Lu (Frontiers in Microbiology, 2024)
Asthma, being the prevailing respiratory ailment globally, remains enigmatic in terms of its pathogenesis. In recent times, the advancement of traditional Chinese medicine pertaining to the intestinal microbiota has yielded a plethora of investigations, which have substantiated the potential of traditional Chinese medicine in disease prevention and treatment through modulation of the intestinal microbiota. Both animal models and clinical trials have unequivocally demonstrated the indispensable role of the intestinal microbiota in the pathogenesis of asthma. This article presents a summary of the therapeutic effects of traditional Chinese medicine in the context of regulating gut microbiota and its metabolites, thereby achieving immune regulation and inhibiting airway inflammation associated with asthma. It elucidates the mechanism by which traditional Chinese medicine modulates the gut microbiota to enhance asthma management, offering a scientific foundation for the utilization of traditional Chinese medicine in the treatment of asthma.